Pengaruh debt to equity ratio (DER), long-term debt to asset ratio (LDAR), dan discretionary accrual terhadap pajak penghasilan badan terutang (Studi pada perusahaan jasa transportasi dan logistik di Bursa Efek Indonesia periode 2019-2023) - Away, Tesalonika Christoffelia; Wokas, Heince R. N.; Rondonuwu, Sintje (Riset Akuntansi dan Portofolio Investasi, 2024)
This study aims to examine the significant effects of the debt to equity ratio (DER), long-term debt to asset ratio (LDAR), and discretionary accrual on corporate income tax payable in transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The study employs a quantitative approach with purposive sampling, resulting in a sample of 11 companies from a total population of 37 companies. Data analysis was conducted using multiple linear regression analysis with the assistance of IBM SPSS 26 software. The results indicate that, partially, the debt to equity ratio (DER) has a positive and significant effect, the long-term debt to asset ratio (LDAR) has no significant effect, while discretionary accrual has a negative and significant effect on corporate income tax payable. Simultaneously, the debt to equity ratio (DER), long-term debt to asset ratio (LDAR), and discretionary accrual have a significant impact on corporate income tax payable.